Penerapan SWOT-QSPM untuk Perancangan Strategi Pengembangan Dimsum Bebas Gluten dari Bandeng dan Kepala Udang: Penelitian - Ahmad Haris Hasanuddin Slamet; Septine Brillyantina; Cindiah Syahnaz; Cicik Retnowati (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The study purpose was to design a development strategy for innovative gluten-free dimsum utilizing local raw materials, specifically milkfish and shrimp head waste in Sidoarjo Regency. This quantitative descriptive research collected primary data through interviews with five experts selected via purposive sampling, comprising academics, practitioners, and entrepreneurs. The analysis employed SWOT (Strengths, Weaknesses, Opportunities, Threats) matrices to map internal and external factors and the Quantitative Strategic Planning Matrix (QSPM) to prioritize development strategies. The IFE matrix indicated the main strength was product innovation based on local potential (score 0.46), while the main weakness was the requirement for freezer storage. The EFE matrix showed the healthy food trend as the greatest opportunity (score 0.53). The product's strategic position lies in Quadrant I (Growth Oriented Strategy). Based on QSPM analysis, the top priority strategy with the highest Total Attractive Score (TAS) of 6.72 is strengthening product branding as a healthy and eco-friendly option. The development of gluten-free dimsum from milkfish and shrimp head waste holds significant potential using aggressive strategies, primarily by strengthening branding to enhance market competitiveness and consumer acceptance.